Dissecting the mediating role of cytokines in the interaction between immune traits and sepsis: insights from comprehensive mendelian randomization - Zheng, Xiangtao; Wang, Yihui; Wang, Yuming; Wang, Xiaofeng; Pei, Lei; Zhao, Shanzhi; Gong, Fangchen; Li, Ranran; Liu, Huan; Liu, Wenbin; Mao, Enqiang; Yang, Zhitao; et al. (Frontiers in Immunology, 2024)
Background: Sepsis is a life-threatening organ dysfunction resulting from a dysregulated host response to infection, yet the potential causal relationship between the immunophenotype and sepsis remains unclear.Methods: Genetic variants associated with the immunophenotype served as instrumental variables (IVs) in Mendelian randomization (MR) to elucidate the causal impact of the immunophenotype on three sepsis outcomes. Additionally, a two-step MR analysis was conducted to identify significant potential mediators between the immunophenotype and three sepsis outcomes.Our MR analysis demonstrated a significant association between the immunophenotype and sepsis outcome, with 36, 36, and 45 the immunophenotype associated with the susceptibility, severity, and mortality of sepsis, respectively. Specifically, our analysis highlighted the CD14+ CD16+ monocyte phenotype as a significant factor across all three sepsis outcomes, with odds ratios (ORs) and corresponding confidence intervals (CIs) indicating its impact on sepsis (OR = 1.047, CI: 1.001-1.096), sepsis in Critical Care Units (OR = 1.139, CI: 1.014-1.279), and sepsis-related 28-day mortality (OR = 1.218, CI: 1.104-1.334). Mediation analyses identified seven cytokines as significant mediators among 91 potential cytokines, including interleukin-5 (IL-5), S100A12, TNFrelated apoptosis-inducing ligand (TRAIL), T-cell surface glycoprotein CD6 isoform, cystatin D, interleukin-18 (IL-18), and urokinase-type plasminogen activator (uPA).Furthermore, reverse MR analysis revealed no causal effect of sepsis outcomes on the immunophenotype.Our MR study suggests that the immunophenotype is significantly associated with the susceptibility, severity, and mortality of patient with sepsis, providing, for the first time, robust evidence of significant associations between immune traits and their potential risks. This information is invaluable for clinicians and patients in making informed decisions and merits further attention.